Incipient seafloor spreading segments: Insights from the Red Sea. Issue 6 (16th March 2016) - Almalki, K. A.; Betts, P. G.; Ailleres, L.
Abstract: Crustal‐scale forward models of marine satellite potential field data suggest that the Red Sea comprises a single segment of ocean crust, which extends along 60% of the Red Sea. The segment "tips" are bounded by continental crust, and there is no evidence for transforms at the segment terminations at the south. These observations indicate that ocean crust formation does not necessarily occur in response to wholesale tearing or "unzipping" of continental lithosphere nor is it necessarily controlled by preexisting transform faults. Ocean crust initiation occurs as a series of isolated segments that coalesce as the basin evolves. The recognition of this process in an orthogonal extension setting is comparable to spreading segmentation in modern ocean systems generated at a highly oblique convergent margin, suggesting that oceanic crust segmentation is not controlled by kinematic boundary conditions. The Red Sea may represent a combination of incipient type I and type II passive margins development. Key Points: Oceanic crust segmentation is not controlled by kinematic boundary conditions Transition in the Red Sea demarcates a change in the style from type I to type II passive margins Microcontinent formation may be created as isolated spreading segments coalesce